Perilaku Pengobatan Sendiri yang Rasional pada Masyarakat - Susi Ari Kristina, Yayi Suryo Prabandari, Riswaka Sudjaswadi (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: Self-medication is defined as used of drugs in community to relieve symptoms of minor illnesses without doctor intervention. Self-medication have many advantages, including safe if properly used and relieve symptom of minor illnesses effectively. Self-medication prevalence in Indonesia in 2005 is 24.1% and in DIY province in 2004 is 87.73%. The behavior of rational self-medication is influenced by sex, age, education level, occupation, income level , knowledge, and positive attitude toward self-medication. The majority of community had low level of self-medication knowledge, therefore health promotion about self-medication is very important to be implemented in community.Method: This was an observational research with cross sectional design that used quantitative method. The number of respondent was 174, and the samples were chosen by multistage random sampling based on the villages number. Data was collected by using structured questionnaire and nonpartisipative observation. The data was analyzed by using independent sample t-test, Pearson correlation and multivariate analysis with multiple logistic regression.Result: The result of the research showed that the majority of respondent’s knowledge was low (52.9%), attitude was bad (57.5%), and self-medication behavior was irrational (67.8%). The result of bivariate analysis showed that there was significant relationship between sex, age, level of knowledge, occupation, income level, knowledge and attitude with rational self-medication behavior. Resident and the distance from health facility were no significant related to rational self-medication behavior. Multivariate analysis result showed that education level was the most influencing rational self-medication behavior at confidence level 95%.Conclusion: There was significant relationship between knowledge and attitude with rational self-medication behavior. Sociodemographic factors that have significant relationship with rational self-medication behavior were sex, age, level of knowledge, occupation and income level. Education level was the most influencing rational self-medication behavior.Keywords: self-medication behavior, knowledge, attitude, sociodemographic factors